Urgensi Pembentukan Hukum Penggunaan Algoritma Rekomendasi Dalam Menciptakan Persaingan Usaha Sehat di Ranah PMSE (RechtJiva, 2024)
This writing is motivated by the existence of a legal vacuum related to the use of recommendation algorithms in trading through electronic systems (PMSE), coupled with the emergence of various problems related to the use of recommendation algorithms in PMSE which can adversely affect business competition in the PMSE realm and threaten small business actors such as UMKM and local traders in Indonesia. The purpose of this paper is to analyze and identify the urgency of regulating the use of recommendation algorithms in PMSE and formulate the right form of regulation in Indonesian legislation. This legal writing uses normative juridical research methods with a statutory approach and conceptual approach. As for the results of this study, first, the realization of the regulation of the use of recommendation algorithms in PMSE is an urgency due to the regulatory vacuum in this field so that it has the potential to cause legal implications in the form of misuse of algorithms by service providers which can threaten the sustainability of local traders and create a climate of unfair business competition in the realm of PMSE in Indonesia. Second, the appropriate form of regulation on the use of recommendation algorithms in PMSE in terms of the Internet Information Service Algorithm Recommendation Management Regulations is to regulate the limits of use, obligations and prohibitions of service providers, as well as the protection of the rights and interests of its users.